2022
DOI: 10.1093/icb/icac136
|View full text |Cite
|
Sign up to set email alerts
|

White Paper: An Integrated Perspective on the Causes of Hypometric Metabolic Scaling in Animals

Abstract: Larger animals studied during ontogeny, across populations, or across species, usually have lower mass-specific metabolic rates than smaller animals (hypometric scaling). This pattern is usually observed regardless of physiological state (e.g. basal, resting, field, maximally-active). The scaling of metabolism is usually highly correlated with the scaling of many life history traits, behaviors, physiological variables, and cellular/molecular properties, making determination of the causation of this pattern cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 210 publications
0
22
0
Order By: Relevance
“…Incisive comparative analyses and controlled experiments, including laboratory and field manipulations of the magnitude of specific RS and RD processes, and artificial selection targeting these specific processes should be especially helpful in determining their relative contribution to metabolic scaling relationships under different conditions [8,29,101,102]. An extraordinarily difficult challenge will be to assess the effects of various factors on the scaling of metabolic rate measured under natural, highly variable field conditions, rather than under artificially controlled conditions in the laboratory, as is usually done [144]. Other useful recommendations for further research can be found in [144].…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
See 4 more Smart Citations
“…Incisive comparative analyses and controlled experiments, including laboratory and field manipulations of the magnitude of specific RS and RD processes, and artificial selection targeting these specific processes should be especially helpful in determining their relative contribution to metabolic scaling relationships under different conditions [8,29,101,102]. An extraordinarily difficult challenge will be to assess the effects of various factors on the scaling of metabolic rate measured under natural, highly variable field conditions, rather than under artificially controlled conditions in the laboratory, as is usually done [144]. Other useful recommendations for further research can be found in [144].…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Furthermore, although traditional theory focusing on the surface law or 3/4-power law has emphasized how physical and geometric constraints on RS and (or) waste removal may cause b to be 2/3 or 3/4 (figure 5b,c), recently many investigators have identified body size-dependent variation in RD by various vital biological structures and processes (e.g. growth, reproduction, locomotion and thermoregulation) as a major cause of variation in b (figure 5d [8,13,25,29,30,43,46,52,53,57,69,[72][73][74]77,101,129,130,144,146]). A RD-centred view has four major advantages over a RS-centred view of metabolic scaling.…”
Section: (F ) Meaningmentioning
confidence: 99%
See 3 more Smart Citations